1993
DOI: 10.1097/00001888-199305000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Changes in studentsʼ attitudes toward HIV-infected patients as the students progress through medical school

Abstract: Overall, the students' responses indicated that over the two years of the study they became more restrictive in their attitudes toward HIV-positive patients, felt less personal obligation toward caring for these patients, and were less likely to use appropriate infection-control methods to ensure their own safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The findings in our study are consistent with previous reports of suboptimal compliance with SP and attitude of HCP towards HIV positivity. [10][11][12] The attitude and practice of being extra careful when a patient is a known HIV positive need to be changed as this makes the HCP less vigilant in handling other patients. CDC recommends that every patient should be treated as potentially infectious and all SP must be taken since many of these patients might be having a hidden infection with these BBP.…”
Section: Discussionmentioning
confidence: 99%
“…The findings in our study are consistent with previous reports of suboptimal compliance with SP and attitude of HCP towards HIV positivity. [10][11][12] The attitude and practice of being extra careful when a patient is a known HIV positive need to be changed as this makes the HCP less vigilant in handling other patients. CDC recommends that every patient should be treated as potentially infectious and all SP must be taken since many of these patients might be having a hidden infection with these BBP.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to first-year students, second-year students were more willing to treat HIV-infected patients, felt a stronger sense of professional obligation, and scored lower on homophobia scales ( p 5 0.05). This is cause for optimism as previous studies showed no changes in attitudes or a declining willingness to treat HIV patients as students advanced through their training (Weyant et al 1993) Medical school provides a unique opportunity to educate future physicians about vulnerable populations such as HIVinfected patients who continue to face social stigma and challenges in access to healthcare. While medical trainees are now more willing to treat patients with HIV than their successors, fear of infection and homophobia remain barriers to patient care that should be addressed in medical curricula.…”
Section: Dear Sirmentioning
confidence: 99%
“…Although questionnaires have been widely used to explore students' attitudes to a range of specific medical issues, such as HIV 56 and drug misuse 57 , those that examine generic attitudes may be of more general applicability. These include the doctor-patient scale 58 , which attempts to discriminate between attitudes that are considered to be doctor-centred and those that are patient-centred.…”
Section: Questionnairesmentioning
confidence: 99%